Environmental heterogeneity has a weak effect on diversity during community assembly in tallgrass prairie - Baer, S. G.; Blair, John M.; Collins, S. L. (My University, 2016)
Understanding what constrains the persistence of species in communities is at the heart of community assembly theory and its application to conserving and enhancing biodiversity. The "environmental heterogeneity hypothesis" predicts greater species coexistence in habitats with greater resource variability. In the context of community assembly, environmental heterogeneity may influence the variety and strength of abiotic conditions and competitive interactions (environmental filters) to affect the relative abundance of species and biodiversity. We manipulated key resources that influence plant diversity in tallgrass prairie (i.e., soil depth and nitrogen availability) to increase environmental heterogeneity prior to sowing native prairie species into a former agricultural field. We compared variability in nutrient availability, aboveground annual net primary productivity (ANPP), and the composition of species between replicate plots containing soil heterogeneity manipulations and plots with no resource manipulations (n = 4 per treatment) during the first 15 yr of community assembly as a test of the "environmental heterogeneity hypothesis." The manipulations increased environmental heterogeneity, measured as the coefficient of variation in NO3-N availability and ANPP. Plant diversity, however, was similar and decayed exponentially and indiscriminately over time between the heterogeneity treatments. Species richness declined linearly over time in both heterogeneity treatments, but richness was higher in the more heterogeneous soil 2 yr following a second propagule addition 8 yr after the initial sowing. As a result, there was a lower rate of species loss over time in the more heterogeneous soil (0.60 species yr(-1)) relative to the control soil (0.96 species yr(-1)). Communities in each treatment exhibited strong convergence over time resulting from a shift in dominant species across all treatments and a gradual increase in the clonal C-4 grass, Andropogon gerardii. We attribute the weak effect of heterogeneity on diversity to increasing dominance of a clonal species, which decreased the scale of soil treatments relative to plant size, dispersal limitation, and absence of a key driver (grazing) known to increase plant diversity under a frequent fire regime. Thus, steering community assembly to attain high biodiversity may depend more on manipulating processes that reduce dominance and facilitate the arrival of new species than promoting environmental heterogeneity.
Citation: Baer, S. G., Blair, J. M., & Collins, S. L. (2016). Environmental heterogeneity has a weak effect on diversity during community assembly in tallgrass prairie. Ecological Monographs, 86(1), 94-106. doi:10.1890/15-0888.1
Keywords: Biodiversity; Carbon Addition; Dispersal; Grassland; Nutrient; Enrichment